THE PERSPECTIVES OF LOCAL WISDOM IN CONSERVATION AND BIODIVERSITY MANAGEMENT OF FISH SPECIES AT RANGAU RIVER, RIAU PROVINCE, INDONESIA - Yustina; Damardi; Irianti, Mitri; Dahnilsyah (International Journal of Educational Best Practices, 2018)
This descriptive research was conducted at Rantau Kopar village, Rokan Hilir District from January to June 2017. The reason for this study is due to the drastic declining of biodiversity of fish species at Rangau river despite the existence  the local wisdom to protect the watershed in the area. It is aimed to discover the perspectives local wisdom in preventing the decreasing of fish biodiversity at  Rangau river. The employed sampling technique was snowball technic sampling which involved 30 respondents. The primary data were obtained using observation and interview; the secondary data (documents). Data consist of community composition, livelihood, community participation in preserving the local wisdom, the synergy between the local wisdom and the policies of the local administration. The data were computed in percentage and were analyzed descriptively. The findings demonstrated that the local wisdom was compiled by the local community whose livelihood as fishermen. Conversely, in 2017, the local people did not comply with both sanction and the local customary law, there had been careless exploitation of the water across the watershed to be oil palm plantation area and the increasing number of oil palm farmers. This study concludes that the main threat facing the local wisdom is that the policies of local administration are not synergic with the local wisdom as stipulated in the regulations and conservation of the area across the watershed of Rangau. The implication of this study is used for the supplementary materials for the bioetnomalay subject in the Indonesian education.